Crisis of Trust in Political Institutions: Challenges and Solutions - Md. Ishaque; Mahmudulhassan Mahmudulhassan; Muhammad Abuzar (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
This study explores the crisis of trust in political institutions, focusing on political parties, governments, and media. The objective is to identify the causes, impacts, and potential solutions to this growing mistrust. The research utilizes a qualitative approach, reviewing existing literature and analyzing case studies from various countries facing political instability and declining public trust. Results indicate that corruption, lack of transparency, misinformation, and limited public participation are primary causes of mistrust. These issues contribute to political instability, decreased voter participation, and increased social division. The discussion highlights the importance of transparency, accurate information, and public involvement in restoring trust. Implications suggest that strengthening political institutions and ensuring accountability are essential for rebuilding public confidence. Recommendations include promoting political education, enhancing media responsibility, increasing public engagement in political processes, and ensuring greater government transparency. The findings emphasize the need for a collaborative effort between the government, media, and the public to address the crisis of trust. This study advocates for the adoption of long-term strategies to restore legitimacy in political institutions, which is critical for maintaining democratic stability and fostering public participation in governance.